Bovine colostrum and its potential contributions for treatment and prevention of COVID-19 - Duman, Hatice; Karav, Sercan (Frontiers in Immunology, 2023)
Bovine colostrum (BC) is the initial milk an animal produces after giving birth, particularly in the first few days. Numerous bioactive substances found in BC, including proteins, enzymes, growth factors, immunoglobulins, etc., are beneficial to human health. BC has a significant role to play as part of a healthy diet, with well-documented health and nutritional advantages for people. Therefore, the use of BC and its crucial derivatives in the development of functional food and pharmaceuticals for the prevention of several diseases such as gastrointestinal and respiratory system disorders is becoming increasingly popular around the world. A novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was identified as the cause of a cluster of pneumonia cases that is called Coronavirus Disease 2019 (COVID-19) in China. After the first SARS-CoV-2 virus-related fatality was announced, the illness quickly spread throughout China and to other continents, causing a pandemic. Since then, numerous studies have been initiated to develop safe and efficient treatments. To prevent viral infection and potential lingering effects, it is important to investigate alternative treatments for COVID-19. Due to its effective bioactive profile and its immunomodulatory roles in biological processes, BC might be considered a promising approach to assist in combating people affected by the SARS-CoV-2 or prevention from the virus. BC has immunomodulatory effects because to its high concentration of bioactive components such as immunoglobulins, lactoferrin, cytokines, and growth factors, etc., which might help control immunological responses, potentially fostering a balanced immune response. Furthermore, its bioactive components have a potential cross-reactivity against SARS-CoV-2, aiding in virus neutralization and its comprehensive food profile also supplies important vitamins, minerals, and amino acids, fostering a healthy immune system. Hence, the possible contributions of BC to the management of COVID-19 were reviewed in this article based on the most recent research on the subject. Additionally, the key BC components that influence immune system modulation were evaluated. These components may serve as potential mediators or therapeutic advantages in COVID-19.